Medicinal plants and practices of Rongkong Traditional Healers in South Sulawesi, Indonesia - Fanie Indrian Mustofa; Nuning Rahmawati; Aminullah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mustofa FI, Rahmawati N, Aminullah. 2020. Medicinal plants and practices of Rongkong Traditional Healers in South Sulawesi, Indonesia. Biodiversitas 21: 642-651. Ethnomedicine reflects the fusion of tradition, natural resources, and local knowledge of the community in maintaining health. However, this knowledge is facing the threat of disappearance due to poor documentation and socio-cultural alteration. This study was conducted to find out information about species of plants used and related practices by traditional healers to overcome health problems. The study was conducted in Rongkong, North Luwu District, South Sulawesi Province. A semi-structured questionnaire was developed to obtain informants demographic data, species of medicinal plants, traditional medicine ingredients, parts used, methods of remedies preparation and use, as well as various ailments that can be treated by medicinal plants. The data were analyzed descriptively and quantitatively, by calculating the family and species use-value. The study revealed medicinal plants used and practices by Rongkong traditional healers to treat 31 ailments. They used a total of 62 species of medicinal plants distributed among 33 botanical families and 55 genera. Allium cepa has the highest UV among all medicinal plants in Rongkong. Both traditional knowledge and medicinal plant diversity possessed by Rongkong community are valuable local assets that must be maintained and developed for greater benefits.